МЕМБРАНИ, МОДИФІКОВАНІ НАНОКОМПОЗИТАМИ ГІДРАТОВАНОГО ДІОКСИДУ ЦИРКОНІЮ ТА ОКИСЛЕНОГО ГРАФЕНУ - Rozhdestvenskaya, Liudmyla; Kudelko, Kateryna; Ogenko, Volodymyr; Bildyukevich, Alexandr; Plisko, Tatiana; Borisenko, Yulia; Chmilenko, V (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
Organo-inorganic membranes were obtained by impregnating ultrafiltration membranes with a composite modifier - zirconium (IV) hydroxide, containing oxidized graphene (0.5 wt.%). The modifier was precipitated in the active layer of the membrane, thus forming a "secondary active layer". The layer thickness calculated according to the Kozeny-Carman equation is 0.66-1.38 μm. A thinner layer is formed in the membrane with smaller pore size. The diffusion coefficients of Li+ and Na+ ions were found. The effect of the modifier on the retention ability relative to hardness ions (10-14%) and to protein compounds (95-98%) during filtration is determined. Mathematical modeling of the dependence of the permeate flux via time showed that the presence of ion exchanger particles in the polymer active layer prevents the accumulation of organic substances in the pores. Therefore, only the outer surface of the membrane is contaminated, and the precipitate can be easily removed mechanically. It was shown that insertion of a carbon component into pores of the membranes, in addition to the inorganic ion-exchangers, is advisable only in the case of a finely porous active layer. In particular, the performance of the initial polymer membrane (20 dm3/m3.h)) and the selectivity to the calibration substance with a molecular weight of 40 kDa (99%) serve as expediency criteria. In comparison with a membrane modified only with inorganic ion exchanger, selectivity is increased, the rate of filtration of protein solutions is higher, and resistance to contamination by organic substances is achieved. The results are discussed from the view of the hydrophobic-hydrophilic properties of oxidized graphene.